The Proletarian and the Political Challenge of Communism on the Australian Left. (1st November 2022) - Hart, Duncan
Abstract : There has been little examination of the theory, ideology and politics of early Australian communism. Findings have been limited by interpretations of "Leninism" that fail to grapple with the Communist International (Comintern) and Bolshevik ideas Australian communists first engaged with from late 1919. A study of The Proletarian, produced in its original iteration between 1920 and 1922, enables historians to understand how the new politics of the Comintern were interpreted in Australia. Communism was conceived as a revolutionary project and strategy centred on mass action that overcame the separation of industrial and political strategies plaguing the radical Left. Communists were called on to organise the class-conscious revolutionary section of the workers to agitate in all aspects of working-class life, including unions and parliament. The meagre analysis of Australian conditions in The Proletarian also provides hints as to why the Communist Party of Australia struggled in its early years.